Observation as a method to enhance collective efficacy: An integrative review. (May 2016) - Bruton, Adam M.; Mellalieu, Stephen D.; Shearer, David A.
Abstract: Objectives: This review provides an integrative argument for the use of observation as an intervention to manipulate individual collective efficacy beliefs in sports teams. Design: An exploration of the conceptual and empirical evidence underpinning observation-based interventions for increasing collective efficacy. Method: A presentation of reflections on the following. First, we reflect on existing techniques used to increase self- and collective efficacy beliefs. Second, we consider collective efficacy in the context of observational learning and the various modeling techniques employed in the sports and motor performance literature. Third, we highlight relevant literature from neuroscience, outlining the analogous neural pathways evident for social cognition (i.e., collective efficacy) and observation. Results: This review presents a case for the use of observation interventions to manipulate collective efficacy, drawing upon social psychological frameworks of human behavior, the observation-based literature, and contemporary understanding of brain and behavior. Conclusions: Observation-based interventions are suited for collective efficacy manipulation in sport. There is a need to advance understanding of this relationship in order to maximize improvements in collective efficacy across group contexts. Highlights: This review recommends observation as a collective efficacy (CE) intervention. Bandura's theories outline the importance of observation in CE development. Observation enhances task performance and self-efficacy, two correlates of CE. Similar neural activity is reported for observation, execution and social cognition. This neuroscience evidence provides further support for observation increasing CE.